(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article presents notes and deviations regarding the accessibility of the clowning and puppets "Circo de Los Pies", as well as finding possibilities in the relationship between the interpreter of Libras and the theatrical scene of animation. The aesthetic and intersemiotic relationship of these figures is understood, placing them in confrontation and in the possibility of creation on stage.